PENGARUH KOMPETENSI SUMBER DAYA MANUSIA, DISIPLIN DAN LINGKUNGAN KERJA TERHADAP PELAYANAN PRIMA PADA DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI KALIMANTAN SELATAN - RUSMINI - (JURNAL KINDAI, 2023)
Rusmini:2011322025810 The Influence of Human Resource Competence, Discipline, Work Environment on Excellent Service at the Manpower and Transmigration Office of South Kalimantan ProvinceThe aim of the research is to find out and analyze the influence of human resource competence, discipline, work environment on excellent service at the Manpower and Transmigration Office of South Kalimantan Province.This type of research uses a quantitative comparative causal approach because in its implementation the researcher looks for the influence between the variables analyzed using appropriate statistical methods, namely the relationship betweenthe independent variables X1, X2 and X3 on the dependent variable Y and there are independent variables. The data analysis technique used is using SPSS.The results showed that Human Resource Competence, Discipline and Work Environment had a significant effect simultaneously on Excellent Service at the Manpower and Transmigration Office of South Kalimantan Province, Human Resource Competence, work discipline and work environment had a partial significant effect on Excellent Service at the Department of Labor Work and Transmigration of South Kalimantan Province, Work Environment with a Dominant Influence on the Office of Manpower and Transmigration of South Kalimantan Province. Keywords: Competence of Human Resources, Discipline, Excellent Service Work Environmen